Improved Long Ureteral Reconstruction With Ileum By Longitudinal Clipping And Mucosal Stripping: An Animal Study - Gu, Hao; Chen, Shulian; Wu, Yubo; Shen, Lei; Luo, Yihang; Li, Xu; Huang, Houjin; Zhao, Zeju (Urology Journal, 2020)
Purpose: To investigate the possibility of bridging long ureteral defects by longitudinal clipping and mucosal stripping of the pedicled segment of ileum (CMSPI). Materials and Methods: Ten beagle dogs (five males and females aged 2-3 years) were used to model a defect of the entire ureter. An ileal segment was selected, and half of the intestinal segment was longitudinally resected, without mesenteric resection. The intestinal mucosa was removed. Then, the ileum was sutured to form a tube connecting the renal pelvis to the bladder. A 5F ureter stent was inserted into the ileum and removed 4 weeks after surgery. Intravenous urography (IVU) was used to observe the reconstructed ureters at 6 and 12 weeks after the operation. Blood samples were collected before surgery and during each radiological examination to assess electrolyte and renal function. Five dogs were randomly euthanized after each IVU. After macroscopic analysis, hematoxylin-eosin (H&E) staining was performed to observe the microscopic changes in the reconstructed ureter. Results: All dogs were in good condition after surgery. Changes in blood electrolyte and renal function after surgery were not significant (Cl- P = .595; Ur P = .852). IVU demonstrated no ureteral obstruction or extravasation of the contrast agent; however, mild hydronephrosis were observed in three dogs. Macroscopic analysis indicated that the reconstructed ureter was intact without strictures. H&E showed that no mucosal structure was present on the luminal surface. Conclusion: CMSPI is feasible for bridging long ureteral defects and has shown good efficacy in this preliminary study.